Найдите значение выражения. Числитель: -2х^4*2^-2 - 5^5 *(25^-1)^2+12^0 Знаменатель: 2^-1

Ответ
[-2х^4 * 2^(-2) - 5^5 * {25^(-1)^2} + 12^0] / 2^(-1) =
=>
-2х^4 * 2^(-2) =
= (-1)*2*2^(-2)*x^4 = (-1)*2^(1-2)*x^4 = (-1)*2^(-1)*x^4
5^5 * {25^(-1)^2 =
= 5^5 * {(5^2)^(-1)}^2 = 5^5 * {5^(-2)}^2 = 5^5 * 5^(-4) = 5^(5-4) = 5^1 = 5
12^0 = 1
=>
[(-1)*2^(-1)*x^4 - 5 + 1] / 2^(-1) =
= [(-1)*2^(-1)*x^4 - 4] / 2^(-1) =
= [(-x^4) /2 - 4]* 2 =
= [(-x^4 - 8)/2]*2 = -x^4 - 8

-2х^4 * 2^(-2) - 5^5 * (25^(-1))^2+12^0 / 2^(-1) = 2*((-x^4)/2 - 5 + 1) = -x^4 - 8 = -(x^4 + 😎
как-то так